RELATIONSHIP BETWEEN PHYSICAL ACTIVITY AND DIET WITH DYSMENORRHOEA DEGREE ON STUDENTS OF THE FACULTY OF HEALTH SCIENCES SEBELAS APRIL UNIVERSITY DURING COVID 19 PANDEMIC IN 2022 - Mentari , Witri Dewi; Nurwanti , Febri (PHSAJ - Public Health Sebelas April Journal, 2022)
Dysmenorrhea is pain or tenderness in the lower abdomen that occurs during a woman’s menstrual cycle. There are several factors that can affect dysmenorrhea, one of which is physical activity and diet, the independent variables in this study are physical activity and diet with the dependent variable being the degree of dysmenorrhea. This study aims to determine the relationship between physical activity and diet with dysmenorrhea degree in Faculty of Health Sciences students, Sebelas April University during COVID-19 pandemic in 2022. This research uses quantitative research method with a cross-sectional observational analytic design. The population in this study were students from the health sciences faculty, amounting to 344 female students with a total sample of 119 female students. The sampling technique used stratified random sampling. The results showed that the frequency of the most dominant degree of dysmenorrhea in the heavy category was 66 respondents (55.5%), light physical activity was the most dominant with 56 respondents (47.1%), and fast food eating patterns were the most dominant in the frequent category with 63 respondents (52.9%). The Chi Square test showed that there is a relationship between physical activity and diet with the degree of dysmenorrhea in students of the Faculty of Health Sciences, Universitas Sebelas April during the COVID-19 pandemic in 2022 with a p-value of 0.000